First report of Alternaria alternata (Fr) Keissler causing leaf spot on Rhus coriarial (sumac) in Syria - الجلاد رنا (Latakia University Journal -Biological Sciences Series, 2022)
Alternaria alternate causes great damage to plantˈs vegetative system which is affected on grouth and productivity. In this study sumacˈs leaves was collected itˈs got dark brown to black spots on it in Wadi Al-ayon area that belonged of Hama governorate in April and May. The pathogen was isolated and the fungusˈs morphological and cultural characteristics were identified and its pathogenicity in sumac and peper leaves separated into petri dishes and artificial infection seedlings on sumac was carried out to verify Kochˈs hypothesis. A pathogenicity of fungi was shown in the study, the symptoms appeared three days after the infection, a week later the spots spreed all over the leaf and turned black, and appeared on the seedlings five days after the infection in the way in nature, and kochˈs hypothesis came true and the spores measurement that was: ( 5.43-18.1×10.86-57.92 µ) so the pathogene is Alternaria alternata and it is the first record of this fungus on sumac trees in Syria.